A study to evaluate the pattern and types of treatment of tibial plateau fracture at BPKIHS Dharan - Rijal, Raju; Shrestha, BP; Khanal, GP; Chaudhary, P; Paneru, S R; Kalawar, RPS; Rai, P (Health Renaissance, 2017)
Background: Tibial plateau fractures occur due to a combination of axial loading and varus/valgus forces leading to articular cartilage damage, mal-alignment and secondary osteoarthritis and functional loss. Objective: To know pattern and types of treatment of tibial plateau fractures and effect of fracture pattern on functional outcome. Method: We conducted prospective study over a period of one year. Fifty-three patients with tibial plateau fractures were presented during that period. Eighteen patients were excluded due to significant polytrauma and major limb injuries. Four patients did not give consent for the study. Thirty-one patients meeting the criteria were enrolled in the study. Two patients were lost during follow up. Remaining patients were evaluated at the end of one year. Data were recorded and analyzed using appropriate statistical methods. Result: Among 29 patients, 21 were male. Mean age was 35.07±11.96 years. 55.2% had RTA followed by 31 percent fall injury. 65% were treated with open reduction and internal fixation with plating followed by AK pop cast, cannulated cancellous screw and ilizarov fixation. Bone grafting was done in 3 cases. Twenty-five patients had excellent, two had good, two had fair and no patients had poor result. Three patients (10%) had complications. One had common peroneal nerve palsy, two had wound infections and no patient demonstrated early arthritic changes. Conclusion: Tibial plateau fractures treated with different modalities at our institute has been associated with excellent and good functional outcome at the end of short term follow up. Health Renaissance 2015;13 (3): 65-72